2019
DOI: 10.21037/mhealth.2019.08.12
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions on using interactive voice response surveys for non-communicable disease risk factors in Uganda: a qualitative exploration

Abstract: Background: Decision-makers need up to date information on risk factors for effective prevention and control of non-communicable diseases (NCDs). Currently available surveys are infrequent and costly to implement. The objective of the study was to explore perceptions on using an interactive voice response (IVR) survey for data collection on NCD risk factors.Methods: Five focus group discussions (FGDs), including rural and urban, elderly and young adults, male and female groups; and eleven key informant intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Intensive information dissemination to generate trust in the survey through other media channels was frequently mentioned by participants including the provision of a contact number and website link to confirm the information provided, learn more about the study or even complain about the survey's experience. Using additional media platforms (television, radio, newspapers) leading up the IVR launch or providing a contact number for the user was also proposed in several studies in Uganda aiming to adequately sensitize communities and mitigate distrust caused by phone calls from unknown numbers [3,11,12]. Other research has identified Colombia as one of the countries where more women than men have reported apprehension towards harassment and security issues (theft or fraud) as principal barriers to mobile phone ownership and usage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intensive information dissemination to generate trust in the survey through other media channels was frequently mentioned by participants including the provision of a contact number and website link to confirm the information provided, learn more about the study or even complain about the survey's experience. Using additional media platforms (television, radio, newspapers) leading up the IVR launch or providing a contact number for the user was also proposed in several studies in Uganda aiming to adequately sensitize communities and mitigate distrust caused by phone calls from unknown numbers [3,11,12]. Other research has identified Colombia as one of the countries where more women than men have reported apprehension towards harassment and security issues (theft or fraud) as principal barriers to mobile phone ownership and usage.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, alternative strategies to enhance the timeliness and reduce the cost of health surveys are needed. One potential solution is to use mobile phone technology, which could reduce implementation and personnel costs and has the potential to provide reliable estimates given widespread coverage [ 1 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive understanding and usability were initially tested at Johns Hopkins University, with persons who identified as being from a low- or middle-income country setting [ 33 ]. A series of key informant interviews (KIIs), focus group discussions (FGDs), and user groups were conducted in each country, and feedback was used to refine and adapt the questionnaire and deployment to the country context [ 34 ]. Audio files of the questionnaire were tested at the country level prior to survey deployment to ensure that translations and recordings were comprehensible.…”
Section: Methodsmentioning
confidence: 99%
“…Records were not maintained on daily clinic attendance, and we were therefore unable to estimate the proportion of clinic attendees who consented to be screened with the EPDS. However, studies have shown that sensitization (i.e., providing information about the study before inviting participation) can result in high levels of voluntary participation [ 41 , 42 ]. In total, 73 perinatal WLHIV consented to complete the depression screening across the five clinics, and 24 (33%) WLHIV scored 10 or greater on the EPDS.…”
Section: Methodsmentioning
confidence: 99%